The BTPABA pancreatic function test in giardiasis. Issue 688 (February 1983) - Okada, M.; Fuchigami, T.; Ri, S.; Kohrogi, N.; Omae, T.
Abstract : The test for exocrine pancreatic function using N-benzoyl-L-tyrosyl-p-aminobenzoic acid (BTPABA test) was assessed in 7 patients with giardiasis and 7 healthy controls. Cumulative percent p-aminobenzoic acid (PABA) recovery in 6 hr was significantly lower in patients with giardiasis, compared with the control group. When an equivalent dose of free PABA was given, there were no differences in PABA recovery between the groups. In patients with giardiasis, the post-treatment values of BTPABA test were significantly higher than the pretreatment values and no differences were found in PABA recovery between patients with giardiasis after eradication and healthy controls. These findings indicate that Giardia lamblia interferes with the action of pancreatic chymotrypsin. It is noteworthy that giardiasis could cause an abnormal BTPABA test.